Peningkatan Mutu dan Produktivitas Melalui Modifikasi Sistem Peralatan Proses pada Usaha Mikro Penghasil Keripik Singkong di Tanjungsiang – Subang - Sudaryanto, Arie (JURNAL PANGAN, 2016)
Processed cassava product as chips is a type of product popularly manufactured by micro enterprises in Subang District. In Tanjungsiang Sub-District, one of the region?s largest cassava producer, there are 10production units of chips producing cassava as raw material at 1 ton of cassava per day. The main equipmentdetermining productivity is a mechanical chopper with an electromotor capacity ranging from 150 to 200 kg/hour. Problems encountered is a long waiting time between chopping and frying process, which canreach 10-30 minutes. Long waiting time resulted in a decrease of quality of cassava chips. Referring tocases faced by cassava chips manufacturer of ?SS? in Tanjungsiang, a modification of cassava chips production system to overcome the problem was designed. The modification was a combination of choppingand frying process. The design was in form of chopper that can be slid by passing a ?rail? placed in parallelto the position of a frying pan. One chopper tools combined in a system with two (2) wok frying. The systemallows chopping and frying to be performed at the same time, and both works can be done consecutivelywithout any time lag. Expected gains from these changes are shorter working time and increased productquality.